Peran Tabungan Dalam Meningkatkan Kesejahteraan Anggota Parselam Makanan Ringan Hari Raya Di Wonocolo Surabaya - Nugraha, Aldy Darmawan; Suryaningsih, Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2019)
The research is qualitative descriptive study that aims to make an illustration regarding to the facts and description in connection with improving of parcel members through wadi’ah contract. This reserach used interview, observation, and documentation as data collection techniques. The study concluded that holiday parcel savings activities can improve the welfare of members as viewed from maqashid sharia indicator which are proctetion of religion (ad-din), protection of life (an-nafs), protection of intellect (al- ‘aql), protection of lineage (an-nasl), protection of property (al-mal). Wadi’ah contract plays a vital role in savings activities, while the understandings of parcel members are inadequate regarding to fiqh muamalah activities that members have done.